Realistic Mathematic Education-Based Student Worksheet to Improve Students' Mathematical Reasoning on Circle Material - Erita, Selvia; Utami, Ecci Siski Dinda; Ningsih, Febria (Universitas Islam Negeri Raden Intan Lampung, 2022)
Mathematical reasoning is a critical feature emphasized in the objective of mathematics education since it may be utilized to solve mathematical problems and other difficulties. This study aims to provide student worksheets based on Realistic Mathematics Education (RME) on circle material that are valid, practical, and useful in increasing students' mathematical reasoning abilities. This research used a 4-D development model. Validation sheets, practicality questionnaires, and test questions were employed as research tools. As a result of this research, the RME-based student worksheet on circle material is declared valid in content/material with an average of 4.05 and constructively valid with an average of 3.85. The practical findings show a value of 80.77% in the practical category. The effectiveness test revealed an N-Gain value of 0.57 with a fairly effective category. It may be concluded that the RME-based student worksheet developed is feasible, practical, and effective. As a result, the RME-based student worksheet can be used in learning to improve students' mathematical thinking abilities.